Improved Sound Absorption Properties in Polyurethane Foams by the Inclusion of Al2O3 Nanoparticles - Binxia Yuan; Xinyi Fang; Jianben Liu; Yan Liu; Rui Zhu (Shock and Vibration)
At present, the scale of China’s power grid is becoming larger and larger, and the control of low-frequency noise in substations (especially for transformers) is very important. The sound-absorbing materials have become one of the important ways to control low-frequency noise. The single polyurethane material cannot satisfy the requirements for reducing low-frequency noise, so it is very necessary to study its composite with other materials. In the paper, the flexible polyurethane foam and Al2O3 nanoparticle composites were obtained by the impregnation method. The method was simple, safe, and easy to control. The morphology and sound absorption coefficient of the foam materials before and after filling were analyzed. Single-hole acoustic cavity models of PU and Al2O3-PU composite were established through the finite element. The absorption and dissipation process of sound pressure for single hole was studied to understand the energy dissipation process. Meanwhile, through studying acoustic energy storage and acoustic energy dissipation, the loss factor of a single hole was obtained, which can predict the change rule of the sound absorption coefficient for PU foam and Al2O3-PU.